Diagnostic sensitivity and specificity of host‐derived salivary biomarkers in periodontal disease amongst adults: Systematic review. (26th December 2019) - KC, Sukriti; Wang, Xiaozhe Z.; Gallagher, Jennifer E.
Abstract: Objective: To systematically assess the diagnostic value of host‐derived salivary biomarkers based on their reported sensitivity and specificity in relation to clinical parameters of periodontal disease diagnosis in adults. Materials and Methods: Comprehensive search of PubMed, Nature, Cochrane and OVID (Embase, MEDLINE [R] and PsycINFO) was conducted up to 1 August 2018, using key terms relevant to the research questions and Cochrane methodology, supplemented by a grey literature search. The revised Quality Assessment of Diagnostic Accuracy Studies (QUADAS‐ 2) tool was used to assess the methodological quality of all included studies. Results: Seven studies were included in the review. Macrophage inflammatory protein‐1αlpha (MIP‐1α), interleukin‐1beta (IL‐1β), interleukin‐6 (IL‐6) and matrix metalloproteinase‐8 (MMP‐8) were identified as diagnostically acceptable biomarkers for periodontal disease. Overall, the combination of IL‐6 and MMP‐8 showed best diagnostic performance. Also, a combination of the four key biomarkers (IL‐1β, IL‐6, MMP‐8 and MIP‐1α) showed promising results for distinction between gingivitis and periodontitis, as well as for periodontitis compared with gingival health. Results are interpreted with caution due to limitations in the number of studies included and their quality. Conclusion: Certain salivary biomarkers can potentially be useful in combination and singularly for the diagnosis of periodontal disease. However, further methodically robust research is required to validate these biomarkers.